2023
DOI: 10.1038/s41545-022-00216-8
|View full text |Cite
|
Sign up to set email alerts
|

A super-efficient polyquaternium gel that can remove over-10-times masses of lignins from wastewater for resourcefulness

Abstract: To address the efficient resourcefulness of papermaking wastewater, this study designed a super-efficient gel material (SGPQG/SGPQ) that could remove over-10-times masses of lignins from wastewater, and subsequently realized the highly-efficient reuse of wastes. The mass of lignin removed by per unit mass of SGPQG/SGPQ was 10,157.71 mg•g-1, i.e., the mass of lignin removed was 10.16 times that of the mass of SGPQG/SGPQ itself, which was 1.23-50.55 times better than the existing similar materials, showing a sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…8). These peaks indicated that carbon-containing C-H, C-N, and C-O bonds, and bonds of montmorillonite and smithsonite were removed from the structure (Hu et al, 2023).…”
Section: Leaching Waste Characterization Analysesmentioning
confidence: 99%
“…8). These peaks indicated that carbon-containing C-H, C-N, and C-O bonds, and bonds of montmorillonite and smithsonite were removed from the structure (Hu et al, 2023).…”
Section: Leaching Waste Characterization Analysesmentioning
confidence: 99%
“…In the author's subsequent studies, it was observed that the introduction of electrostatic adsorption could overcome the pore size limitation of activated carbon. Additionally, compared with the physical adsorptions based on van der Waals forces, the electrostatic adsorption (chemical adsorption) could form stronger chemical bonds between the adsorbent and adsorbate (e.g., anion-cation electrostatic ionic bonds), achieving efficient adsorption ability towards some pollutants with large molecular volumes [20][21][22][23][24] . The authors found that, based on the strong electrostatic structures of polyquaternium gel adsorbents, the adsorption capacity of dyes with large molecular volumes (Reactive Scarlet 3BS) increased by a factor of 741.10 compared to commonly used activated carbon.…”
mentioning
confidence: 99%